2020
DOI: 10.1186/s13063-020-04254-w
|View full text |Cite
|
Sign up to set email alerts
|

Methods for safety and endpoint ascertainment: identification of adverse events through scrutiny of negatively adjudicated events

Abstract: Background: The primary goal of phase 2 and 3 clinical trials is to evaluate the safety and effectiveness of therapeutic interventions, and efficient and reproducible ascertainment of important clinical events, either as clinical outcome events (COEs) or adverse events (AEs), is critical. Clinical outcomes require consistency and clinical judgment, so these events are often adjudicated centrally by clinical events classification (CEC) physician reviewers using standardized definitions. In contrast, AEs are rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Although Pogue et al 5 and Harper et al 25 observed that the conclusions drawn from some trials might not be impacted with and without adjudication, event adjudication has remained as a fundamental component of clinical trials. [1][2][3][4][5][6][7][8][9][10][11][12][13] Since Nolen et al, 1 Zhao and Pauls, 11 and Kuurstra et al 12 introduced web-based computer systems to automate the coordination of the process, there has been no progress on automating the evaluation of events. Sharma et al 13 reviewed issues rising from event adjudication and called for incorporating technological breakthroughs into the process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Pogue et al 5 and Harper et al 25 observed that the conclusions drawn from some trials might not be impacted with and without adjudication, event adjudication has remained as a fundamental component of clinical trials. [1][2][3][4][5][6][7][8][9][10][11][12][13] Since Nolen et al, 1 Zhao and Pauls, 11 and Kuurstra et al 12 introduced web-based computer systems to automate the coordination of the process, there has been no progress on automating the evaluation of events. Sharma et al 13 reviewed issues rising from event adjudication and called for incorporating technological breakthroughs into the process.…”
Section: Discussionmentioning
confidence: 99%
“…To assess outcomes objectively and consistently, central blinded event adjudication is commonly used in the conduct of clinical trials. [1][2][3][4][5][6][7][8][9][10][11][12][13] In this context, adjudication is a process to evaluate whether site-reported events are aligned with definitions given in study protocols or not. Although Nolen et al, 1 Zhao and Pauls, 11 and Kuurstra et al 12 discussed automating the communication between a clinical-data-and-coordination center and an event adjudication committee, their evaluation of outcomes still requires 100% human efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Hospitalization due to ALS progression was defined as AEs that met all three of the following conditions in the case report form: (1) “Seriousness”—Yes; (2) “Admission to a hospital or prolongation of existing hospitalization for treatment”—Yes; and (3) “Does it fall under aggravation of symptoms associated with progression of primary disease (i.e., ALS)?”—Yes 11 …”
Section: Methodsmentioning
confidence: 99%
“…(1) "Seriousness"-Yes; (2) "Admission to a hospital or prolongation of existing hospitalization for treatment"-Yes; and (3) "Does it fall under aggravation of symptoms associated with progression of primary disease (i.e., ALS)?"-Yes. 11 The endpoints were specified in this post hoc manner as follows:…”
Section: Post Hoc Analysesmentioning
confidence: 99%
“…Adverse events (AEs) represent off-target occurrences that may or may not be associated with the drug or product under investigation. Phase I trials are often solely concerned with safety and may therefore not have a control group, as the aim is not to show efficacy of the drug in question [65]. The aim of phase I trials is often to determine maximum tolerated dose (MTD), which is the highest dose that does not cause unacceptable side effects.…”
Section: Safetymentioning
confidence: 99%